DURUUSU AL-LUGHAH AL-ARABIYAH AL-JUZ AL-AWWAL FII TATWIIRI TA’LIIMI AL-LUGHAH AL-ARABIYAH - Anyes Latifatul Insaniyah; M. Nailul Hamam (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2020)
Textbooks are all forms of material used to assist teachers in carrying out teaching and learning activities in class. Educational material is the most important thing in the teaching and learning process and is a factor that affects the quality of education. The text book "Durus Al-Lughah" Juz 1 is a textbook written by Mahmud Yunus. This study aims to apply the textbook "Durus Al-Lughah" Juz 1 in class 1 of Sunan Ampel Full Day Junior High School in the development of Arabic language learning and the supporting factors in its use to develop Arabic learning. This type of research is a descriptive study with a qualitative approach. The results of this study indicate that the application of the textbook "Durus Al-Lughah" Juz 1 through planning, implementation and evaluation. In the lesson planning, the teacher has included learning materials in the curriculum and lesson plans. In implementing learning, Arabic teachers apply Arabic learning methods, strategies and media. Assessment is done through traditional observation, questions and discussion. The supporting factor in using the textbook "Durus Al-Lughah" Juz 1 in in class 1 of Sunan Ampel Full Day Junior High School is the existence of an Arabic language environment.